Konsep Amal Jariah Menurut Agama-agama di Indonesia: Sebuah Kajian Teologis, Filosofis, dan Praktis - Monady, Hanief; Jaki, Akhmad; Husnul; Rofi'i, Rofi'i; Mobarak, Najih (Jurnal Ilmiah Ilmu Ushuluddin, 2024)
The concept of amal jariah, meaning "charity that provides sustainable benefits," is a universal principle in major religions such as Islam, Hinduism, Buddhism, Christianity, and Confucianism. This research explores this concept from theological, philosophical and practical perspectives in these religions. Through a comprehensive literature review, primary and secondary sources are used to understand the essence and implications of this concept. The literature review approach allows researchers to explore the concept of charity without the limitations of field research. Charity in Islam includes good actions that continue to benefit others, reflecting human values and social justice. Karma in Hinduism regulates a person's fate based on their actions, influencing this life and the next. In Buddhism, a balance between karma and virtue is important in achieving wisdom and liberation. In Christianity, kindness and love are central principles that reflect God's love for humans. In Confucianism, the concept of Ren emphasizes the values of compassion and benevolence. Social welfare in religions is creating conditions where every individual feels safe, valued, and has a fair chance in life. The principles of humanity, justice and service to others are recognized as universal values in an effort to create a just, harmonious and empathetic society. In conclusion, a deep understanding of the concept of charity from various religions can enrich collaboration between religious communities in building a better world.